FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNAAN LAYANAN TELEMEDICINE PADA MASA PANDEMI COVID-19 DI PULAU JAWA - Maylin Djuana Siboro; Antono Surjoputro; Rani Tiyas Budiyanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
The spread of COVID-19 in Indonesia has prompted the government to urge health agencies to develop telemedicine and direct people to minimize activities outside the home, including visiting health services. In its implementation, the use of telemedicine has increased rapidly even though it is still in the development stage and there is no specific regulation. Java Island as a region with a high number of COVID-19 cases has the potential to utilize telemedicine. The purpose of this study was to analyze the factors that influence the use of telemedicine during the COVID-19 pandemic on the island of Java. This research is a quantitative study with a cross-sectional approach. Respondents of the study were 269 people using the incidental sampling method. The results of this study indicate factors related to the use of telemedicine services during the Covid-19 period in Java, namely knowledge (p = 0.000), attitude (p = 0.000), trust (p = 0.000), accessibility (p = 0.000), role environment (p = 0.000), individual health assessment (p = 0.000), and perceived benefits (p = 0.006). Meanwhile, the unrelated factor was the perception of obstacles (p = 0.090). It is recommended that the government formulate telemedicine regulations related to patient protection guarantees, medical record safety, information and communication technology standards, and quality assurance. The health office conducts telemedicine education to the public and supervises telemedicine providers to ensure that services remain integrated with the health facilities.